Introduction of a bead beating step improves fungal DNA extraction from selected patient specimens - Sebastian Scharf; Anna Bartels; Mustafa Kondakci; Klaus Pfeffer; Birgit Henrich; Rainer Haas (Elsevier, 2020)
In immunocompromised patients a colonisation with fungi carries the risk to develop serious invasive fungal infection. An early detection is therefore important, but not optimal hitherto. Fortunately, molecular genetic methods have increased the sensitivity of fungal detection and limited the time, until results are available. However, their success depends on an efficient extraction of genomic DNA from the fungal cell in the given diagnostic specimen.To improve the routine DNA preparation method for yeasts and moulds, the impact of bead beating on fungal DNA release was evaluated. PBS, blood and respiratory rinse were spiked with Candida glabrata or Aspergillus fumigatus. DNA was extracted by mechanical bead beating in addition to the different steps of the DNA preparation protocol, which comprised liquid nitrogen treatment, proteinase K digestion and DNA isolation using the EZ1 DNA Tissue Kit and Workstation. In every method variant tested, treatment with liquid nitrogen did not improve the DNA release. Bead beating once followed by proteinase K digestion and EZ1-work-up led to the highest DNA release from fungus, spiked in PBS, and increased the extracted DNA amount of C. glabrata about 100-fold and of A. fumigatus about 10-fold in relation to sole EZ1-work-up. In fungus-spiked respiratory rinse and blood, highest increase in DNA release was measured after triple bead beating with simultaneous proteinase K digestion. Fungal DNA release of C. glabrata increased for >100-fold in respiratory rinse and for >1000-fold in blood and of A. fumigatus for >10-fold in respiratory rinse and about 5- to 10-fold in blood.The data of this study clearly demonstrate that preparation of fungal DNA from human specimens is optimized by introduction of a bead beating step to the conventional DNA-preparation method without the necessity of a liquid nitrogen step.